Enkele persoonlikheidskenmerke by essensiele hiperteimsie-kleurlingvroue - A.M. Venter (AOSIS, 1980)
From a review of the literature on essential hypertension it appears that there is lack of clarity in respect of the causes of this condition. Apparently the disease is associated with genetic, environmental and personality factors, but the interaction between factors such as mother-dominance, the handling of aggression and rage and motivation could have a bearing on the situation. The objective of this research was therefore to investigate these factors by comparing a group of 50 hypertensive and a group of 40 normotensive Coloured women.